Surface and interface study of U/Si (111) - Chen, Qiuyun; Feng, Wei; Zhu, Xiegang; Luo, Lizhu; Xie, Donghua; Tan, Shiyong; Lai, Xinchun (Applied surface science, 2014)
Thin uranium films were deposited on Si (111)-77 surface by e-beam evaporation. The surface and interface of U/Si (111) with different annealing temperatures were studied by scanning tunneling microscopy (STM), low-energy electron diffraction (LEED), reflection high energy electron diffraction (RHEED) and photoemission spectroscopy. The formation of 2D uranium silicide (USi1.67) film was confirmed by the presence of a sharp 11 LEED pattern, and the surface morphology of this phase displays triangular layered structures. A new superstructure was found for the U-Si system when annealing the interface at 1000K. Further annealing of the interface leads to the appearance of large area of Si (111)-77 reconstruction surface with high islands on it.